Strategic Insights Into Social Media Marketing Activities For Transportation Businesses - Roosdhani, Mohamad Rifqy; Komaryatin, Nurul; Arifin, Samsul; Khoiruddin, Muhammad; Ali, Ali; Huda, Nurul (International Journal of Economics, Business and Innovation Research, 2025)
In this study, the function of Social Media Marketing Activities (SMMA) as a dynamic capability in influencing Social Ties, Purchase Decisions, and the moderating impact of Brand Love within the transportation services industry, focusing on PO Bejeu. Unlike previous research primarily centered on retail or cosmetics, transportation services present distinct operational challenges that merit deeper exploration. Using data from 103 respondents collected via a Likert scale Google form questionnaire, the study employed Analysis using Structural Equation Modelling (SEM) with SmartPLS 4.0 software. Results revealed that SMMA significantly improves Social Ties (path coefficient = 0.630) and Purchase Decisions (path coefficient = 0.404), with Social Ties mediating the effect on Purchase Decisions (indirect effect = 0.114). Brand Love amplifies the relationship between Social Ties and Purchase Decisions (interaction effect = 0.134). These findings underscore SMMA's effectiveness in fostering customer engagement, enhancing brand trust, and driving personalized strategies to improve purchase decisions. Moreover, nurturing emotional connections via Brand Love strengthens customer loyalty and advocacy. The research emphasises the transformative potential of SMM for transportation services, offering actionable insights to leverage social platforms to deepen consumer relationships and boost business growth in industries with lower digital marketing adoption rates.